Chronic migraine: history, imaging and patient characteristics, and controversies - Tepper, Stewart J. (Henry Stewart Talks, 2024)
Chronic migraine, Chronic Daily Headache (CDH), Transformed Migraine (TM), Silberstein-Lipton approach, ICHD-3 Criteria for MOH, Chronic Tension-Type Headache (CTTH), Boundary between CM and EM, New proposed CM criteria, Onabot responders, Anti-CGRP therapy